(untitled) (Research, Society and Development, 2022)
Objective: To describe the epidemiological profile of violence against the elderly in a state in the northeast region of Brazil. Methodology: Quantitative, descriptive, retrospective study, carried out with information available in a database of the Diseases Information System and Notification, from 2008 to 2018. Data analysis was performed using simple statistics (frequency and percentage). Results: 1,535 violence notification forms were analyzed, with a large number of ignored and blank notifications. Regarding the characteristics of the elderly, 63.4% were men, 34.8% of mixed race, 23.8% with an education level between illiterate and elementary school, 71.9% victims of physical violence, 41, 3% through physical force/beating, 56.8% of the violence occurred in the urban area, 37.9% in the victim’s own residence, 74.4% classified as interpersonal and 37.2% were notified by emergency units. Conclusion: Violence against elderly people occurred mainly in men, who were literate and who were victims of physical force/beating. This study shows that the incompleteness of information in filling out the notification form reveals the need for a broader view of the health team for the complete recording of data.